2017
DOI: 10.1021/acs.jpcc.7b06242
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Containing Zwitterionic Poly(Ionic Liquid)s as Polymer Electrolytes for Lithium-Ion Batteries

Abstract: Polymer electrolytes are considered as the good candidates for the new-generation-safe lithium-ion battery. Herein, a free-standing and flexible polymer electrolyte film based on a lithium-containing zwitterionic poly­(ionic liquid) (PIL) was constructed with and without propylene carbonate (PC) by in-situ photopolymerization. In this system, the lithium-containing IL synthesized by equimolecular neutralization of imidazolium-type zwitterion 3-(1-vinyl-3-imidazolio)­propanesulfonate (VIPS) and lithium bis­(tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 56 publications
1
45
0
Order By: Relevance
“…A few studies have sought to clarify the fundamental mechanisms underlying ion transport in polyZIs . In this context, we note a study reported by Ohno and coworkers, which highlighted a surprising impact of polymer architecture on ionic conductivity .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…A few studies have sought to clarify the fundamental mechanisms underlying ion transport in polyZIs . In this context, we note a study reported by Ohno and coworkers, which highlighted a surprising impact of polymer architecture on ionic conductivity .…”
Section: Introductionmentioning
confidence: 75%
“…Their ionic properties and hydrophilicity have made them targets for use in organic electronics, catalysis, battery electrolytes, surfactants, drug‐delivery, and antifouling coatings, among other applications . ZI‐incorporated polymers (polyZIs) have also been investigated as novel materials for chromatography, drug‐delivery, self‐assembled microstructures, and battery electrolytes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[221] This zwitterion-based IL showed high thermal stability with decomposition temperature around 300 °C. [223] The zwitterion-based IL was prepared from imidazolium-type zwitterion 3-(1-vinyl-3-imidazolio)-propanesulfonate (VIPS, www.advancedsciencenews.com Scheme 8) and LiTFSI. [222] The mixtures were composed of an IL 1-butyl-1-methyl-pyrrolidinium bis(trifluoromethyl-sulfonyl)imide (BMP-TFSI), a Li salt (LiTFSI), and different concentrations of zwitterions, 1-(1-butylpyrrolidinium)butane-4-sulfonate (ZN) (Scheme 8) or 1-(1-trin-butylphosphonium)butane-4-sulfonate (ZP) (Scheme 8).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[221] To gain more insight about the transportation of ions in the ternary mixture (IL/Li salt/zwitterions), the effect of sulfonate-based zwitterions addition on different properties (thermodynamic, ion transport and electrochemical) of ionic liquid/Li-TFSI mixtures was investigated. [223] This IL can be applied to sustain mechanical strength and to form Li + rich channels for the transportation of Li + . The ternary mixtures demonstrated an anodic stability up to 5-6 V versus Li + /Li.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%